Liquiritin Attenuates Lipopolysaccharides-Induced Cardiomyocyte Injury via an AMP-Activated Protein Kinase-Dependent Signaling Pathway - Mou, Shan-Qi; Zhou, Zi-Ying; Feng, Hong; Zhang, Nan; Lin, Zheng; Aiyasiding, Xiahenazi; Li, Wen-Jing; Ding, Wen; Liao, Hai-Han; Bian, Zhou-Yan; Tang, Qi-Zhu (Frontiers in Pharmacology, 2021)
Background: Liquiritin (LIQ) is a traditional Chinese medicine that has been reported to regulate inflammation, oxidative stress and cell apoptosis. However, the beneficial effects of LIQ in lipopolysaccharides (LPS)-induced septic cardiomyopathy (SCM) has not been reported. The primary goal of this study was to investigate the effects of LIQ in LPS-induced SCM model. Methods: Mice were pre-treated with LIQ for 7 days before they were injected with LPS (10 mg/kg) for inducing SCM model. Echocardiographic analysis was used to evaluate cardiac function after 12 h of LPS injection. Thereafter, mice were sacrificed to collect hearts for molecular and histopathologic assays by RT-PCR, western-blots, immunohistochemical and terminal deoxynucleotidyl transferase nick-end labeling (TUNEL) staining analysis respectively. AMPKα2 knockout (AMPKα2−/−) mice were used to elucidate the mechanism of LIQ Neonatal rat cardiomyocytes (NRCMs) treated with or without LPS were used to further investigate the roles and mechanisms of LIQ in vitro experiments. Results: LIQ administration attenuated LPS-induced mouse cardiac dysfunction and reduced mortality, based upon the restoration of EF, FS, LVEDs, heart rate, dp/dt max and dp/dt min deteriorated by LPS treatment. LIQ treatment also reduced mRNA expression of TNFα, IL-6 and IL-1β, inhibited inflammatory cell migration, suppressed cardiac oxidative stress and apoptosis, and improved metabolism. Mechanistically, LIQ enhanced the phosphorylation of AMP-activated protein kinase α2 (AMPKα2) and decreased the phosphorylation of mTORC1, IκBα and NFκB/p65. Importantly, the beneficial roles of LIQ were not observed in AMPKα2 knockout model, nor were they observed in vitro model after inhibiting AMPK activity with an AMPK inhibitor. Conclusion: We have demonstrated that LIQ exerts its protective effects in an SCM model induced by LPS administration. LIQ reduced inflammation, oxidative stress, apoptosis and metabolic alterations via regulating AMPKα2 dependent signaling pathway. Thus, LIQ might be a potential treatment or adjuvant for SCM treatment.